2007
DOI: 10.1063/1.2796174
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of pattern formation during the catalytic oxidation of CO on Pt{100} at low pressures

Abstract: Theoretical studies have thus far been unable to model pattern formation during the reaction in this system on physically feasible length and time scales. In this paper, we derive a computational reaction-diffusion model for this system in which most of the input parameters have been determined experimentally. We model the surface on a mesoscopic scale intermediate between the microscopic size of CO islands and the macroscopic length scale of pattern formation. In agreement with experimental investigations ͓M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Platinum is a precious and expensive noble metal commonly used as a catalyst in numerous chemical reactions. For example, Pt is the most efficient catalyst in hydrogen-fuel cells and in CO oxidation. Hence, lowering the amounts of Pt at the catalytic surface is a critical mission for technology transfer. Indeed, generally it has been reported that bimetallic alloys have superior catalytic properties with respect to the pure metal. As an example, Stamenkovic and co-workers have reported that the Pt 3 Ni(111) surface is more active than Pt(111) and current state-of-the-art Pt/C catalysts for the oxygen reduction reaction in fuel cells .…”
Section: Introductionmentioning
confidence: 99%
“…Platinum is a precious and expensive noble metal commonly used as a catalyst in numerous chemical reactions. For example, Pt is the most efficient catalyst in hydrogen-fuel cells and in CO oxidation. Hence, lowering the amounts of Pt at the catalytic surface is a critical mission for technology transfer. Indeed, generally it has been reported that bimetallic alloys have superior catalytic properties with respect to the pure metal. As an example, Stamenkovic and co-workers have reported that the Pt 3 Ni(111) surface is more active than Pt(111) and current state-of-the-art Pt/C catalysts for the oxygen reduction reaction in fuel cells .…”
Section: Introductionmentioning
confidence: 99%
“…There can also be the formation of spatial patterns on the catalyst surface 31 , and these have been modelled recently within a sophisticated reaction-diffusion scheme32 . Although we are not aware of any literature concerning oscillatory reactions on Ir{100}, the experimental findings by Ali et al suggest that such oscillatory behavior may be present at temperatures above 900 K.…”
mentioning
confidence: 99%
“…Intermolecular forces, substratemediated interactions, and even blocking of adjacent sites by adsorbates are all factors that may cause the surface diffusion coefficients to vary with coverage [5,6]. Other nontrivial coupling modes have also been invoked [7,8].…”
Section: Introductionmentioning
confidence: 99%